Advances in Nanotechnology as a Potential Alternative for Plant Viral Disease Management - Dutta, Pranab; Kumari, Arti; Mahanta, Madhusmita; Biswas, K. K.; Dudkiewicz, Agnieszka; Thakuria, D.; Abdelrhim, Abdelrazek S.; Singh, S. Basanta; Muthukrishnan, Gomathy; Sabarinathan, K. G.; Mandal, Mihir K.; Mazumdar, N. (Frontiers in Microbiology, 2022)
Plant viruses cause enormous losses in agricultural production accounting for about 47% of the total overall crop losses caused by plant pathogens. More than 50% of the emerging plant diseases are reported to be caused by viruses, which are inevitable or unmanageable. Therefore, it is essential to devise novel and effective management strategies to combat the losses caused by the plant virus in economically important crops. Nanotechnology presents a new tendency against the increasing challenges in the diagnosis and management of plant viruses as well as plant health. The application of nanotechnology in plant virology, known as nanophytovirology, includes disease diagnostics, drug delivery, genetic transformation, therapeutants, plant defense induction, and bio-stimulation; however, it is still in the nascent stage. The unique physicochemical properties of particles in the nanoscale allow greater interaction and it may knock out the virus particles. Thus, it opens up a novel arena for the management of plant viral diseases. The main objective of this review is to focus on the mounting collection of tools and techniques involved in the viral disease diagnosis and management and to elucidate their mode of action along with toxicological concerns.